Leading With Compassion - Dias Prasongko; Wigke Capri Arti (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2021)
This article elaborates on two important elements of women's leadership. First, it explores how leadership theory has abandoned its masculine perspective in favour of a